2019
DOI: 10.1111/jam.14332
|View full text |Cite
|
Sign up to set email alerts
|

New sequential‐touch method to determine bacterial contact transfer rate from finger to surface

Abstract: Aims Infection can occur via surface touch. A new method was developed to more accurately evaluate the bacterial transfer rate from a finger to a surface. Methods and Results Staphylococcus aureus was used as the model bacteria to inoculate a thumb. Sequential touches were made between the contaminated thumb and a series of clean microscope slides. The bacteria on the glass surface were cultured in situ, and the bacterial transfer rate was evaluated by fitting the colony‐forming units (CFUs) on glass surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…The above data enabled us to develop the first mechanism-based model for predicting the rate of microbial transfer via surface touch. The new model, which was based on several of our previous studies, ,,, introduces new definitions of transferring events and embodies new concepts, such as “equilibrium” and “full touch”. This model successfully captures the effects of some important physical factors on the transfer rate, as summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above data enabled us to develop the first mechanism-based model for predicting the rate of microbial transfer via surface touch. The new model, which was based on several of our previous studies, ,,, introduces new definitions of transferring events and embodies new concepts, such as “equilibrium” and “full touch”. This model successfully captures the effects of some important physical factors on the transfer rate, as summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated microbial transfer during defined sequential touches and repeated touches. In previous studies, , we used the sequential-touch method to calculate the transfer rate more accurately, without needing to evaluate the donor microbial concentration . For repeated touches, the concept of equilibrium is not novel. ,, However, eq reveals that the equilibrium depends only on P A , whereas the speed of reaching the equilibrium is determined by both P A and P T .…”
Section: Discussionmentioning
confidence: 99%
“…During this contact process, the physical parameters remain unchanged, and thus it was assumed that the transfer efficiency, τ, of the fluorescent solution was constant during the continuous stepping process, and that the fluorescent solution on the effective contact area of the sole was completely transferred. Zhao et al [26] confirmed this hypothesis in the process of sequential hand contact, and τ was calculated as follows:…”
Section: Analysis Of the Propagation And Diffusion Influencing Factorsmentioning
confidence: 88%
“…Zhao and Li (2019) developed a sequential touch surface method to avoid common issues of surface sampling such as large standard deviations among trials. In Study 3 ( sequential transfer to surface‐to‐skin ) of the current research, significant differences were observed in the number of sequential transfer events observed from fomite‐to‐skin for plastic, touchscreen and vinyl, which further supports data from the previous studies in that surface type impacts transfer rates.…”
Section: Discussionmentioning
confidence: 99%
“…Demarcated thumbpads were inoculated with 2 μl of Φ6, and immediately (<15 s) pressed to a surface placed on a triple beam balance scale (Ohaus® Harvard Trip Balance) set to 800 g pressure (Zhao & Li, 2019). The six surface types were used in a different order for each trial to minimize the impact of handwashing frequency on transfer rates (Kownatzki, 2003).…”
Section: Methodsmentioning
confidence: 99%